Criticism of Islamic Feminism towards Patriarchy in Islamic Family Law in Indonesia - Burhanuddin, Ahmad; Muhammadong, Muhammadong; Ubaidillah, M. Bahtiar; Swandana, Irwan (Westscience Press, 2025)
This study critically examines the perspectives of Islamic feminists on patriarchal elements embedded in Islamic family law in Indonesia. Using a qualitative approach, the research draws insights from five key informants, including scholars, activists, and legal practitioners engaged in Islamic feminist discourse. The findings reveal that patriarchal interpretations—particularly regarding male guardianship, polygamy, divorce, and inheritance—are rooted in socio-cultural biases rather than Islamic theological principles. Islamic feminists advocate for contextual reinterpretation (ijtihad) of religious texts to restore the egalitarian spirit of Islam. Through public education, legal advocacy, and collaboration with religious leaders, they promote reform efforts that challenge institutional resistance and conservative narratives. This study contributes to the broader discourse on gender justice in Muslim-majority societies by highlighting the transformative potential of Islamic feminism in reimagining family law in alignment with Islamic ethical values and contemporary gender equality.